2018
DOI: 10.1111/pcmr.12688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a series of 990 index patients with albinism

Abstract: Albinism is a clinically and genetically heterogeneous disease characterized by variable degrees of hypopigmentation and by nystagmus, foveal hypoplasia, and chiasmatic misrouting of the optic nerves. The wide phenotypic heterogeneity impedes the establishment of phenotype-genotype correlations. To obtain a precise diagnosis, we screened the 19 known albinism genes in 990 index patients using targeted next-generation sequencing (NGS) and high-resolution comparative genomic hybridization. A molecular diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
199
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(227 citation statements)
references
References 28 publications
(36 reference statements)
10
199
1
Order By: Relevance
“…In previous reports, hair color presentation varied from white to dark, with the blond/light brown color being the most common. Skin color ranged from unpigmented to pigmented and the most common color was fair/pale, whereas iris color ranged from light to dark brown and was most frequently blue, green or gray . Our three Chinese OCA6 patients exhibited fair skin with light blond to light brown hair, which is very close to that of the majority of patients from other races but without the manifestations of either extreme light or dark color.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In previous reports, hair color presentation varied from white to dark, with the blond/light brown color being the most common. Skin color ranged from unpigmented to pigmented and the most common color was fair/pale, whereas iris color ranged from light to dark brown and was most frequently blue, green or gray . Our three Chinese OCA6 patients exhibited fair skin with light blond to light brown hair, which is very close to that of the majority of patients from other races but without the manifestations of either extreme light or dark color.…”
Section: Discussionsupporting
confidence: 56%
“…Notably, a small insertion, c.571_572insATTA, identified in an Indian patient did not result in ocular defects, suggesting it is a variant form of OCA6 . The splicing mutation (c.590+4A>G) has been detected in three unrelated OCA6 patients and the nonsense mutation (c.216T>A/G) has been detected in another three unrelated patients . These may represent high‐frequency SLC24A5 mutations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…HPS‐8 was first reported in an extended consanguineous Pakistani family with six affected individuals; autozygosity mapping assisted in identifying a homozygous frameshift variant, c.448delC (p.Gly150Argfs*75), in BLOC1S3 in all affected individuals (Morgan et al, 2006). Three additional HPS‐8 cases with homozygous pathogenic BLOC1S3 variants have since been reported (Cullinane et al, 2012; Lasseaux et al, 2018; Table 9; Figure 7).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of HPS‐related genes in genetic screening panels of cohorts with clinical features of HPS has resulted in the recent identification of groups of undiagnosed HPS subjects, especially those with milder clinical phenotypes. Targeted sequencing of 990 cases with albinism identified 46 HPS subjects (Lasseaux et al, 2018). A similar study of 21 Arabian individuals with ocular hypopigmentation identified 10 HPS subjects (Khan et al, 2016), a study of 46 Japanese cases with (OCA‐1 and HPS‐1 negative) albinism identified nine HPS subjects (Okamura et al, 2019), and a study of Chinese hypopigmentation cases identified 10 HPS subjects (Wei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%